2013
DOI: 10.1016/j.jconrel.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Thiomer-coated liposomes harbor permeation enhancing and efflux pump inhibitory properties

Abstract: An ideal oral drug carrier should facilitate drug delivery to the gastrointestinal tract and its absorption into the systemic circulation. To meet these requirements, we developed a thiomer-coated liposomal delivery system composed of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) and a maleimide-functionalized lipid, to which chitosan-thioglycolic acid (CS-TGA) was covalently coupled. In addition to conventional 77 kDa CS-TGA (CS-TGA77), we tested the 150 kDa homologue (CS-TGA150) as well as an S-protecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…These results indicate that the presence of P-gp in the membrane increased the passive membrane permeability of Rho123, even when active transport was not enabled. The median P s of Rho123 across GUV membranes without P-gp (9.9 × 10 −10 m s −1 ) is approximately one order of magnitude smaller than a previously reported P s value of Rho123 diffusion across liposome membranes [55] and approximately two orders of magnitude smaller than the P s value across basolateral membranes of MDCK cells (1 × 10 −7 m s −1 ) [56] as well as the reported P s values of other known P-gp substrates. For example, P s values for vincristine, vinblastin, and verapamil across the apical membrane of Caco-2 cells were 3.3 × 10 −9 , 1.8 × 10 −7 , and 5.2 × 10 −6 m s −1 , respectively [57].…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…These results indicate that the presence of P-gp in the membrane increased the passive membrane permeability of Rho123, even when active transport was not enabled. The median P s of Rho123 across GUV membranes without P-gp (9.9 × 10 −10 m s −1 ) is approximately one order of magnitude smaller than a previously reported P s value of Rho123 diffusion across liposome membranes [55] and approximately two orders of magnitude smaller than the P s value across basolateral membranes of MDCK cells (1 × 10 −7 m s −1 ) [56] as well as the reported P s values of other known P-gp substrates. For example, P s values for vincristine, vinblastin, and verapamil across the apical membrane of Caco-2 cells were 3.3 × 10 −9 , 1.8 × 10 −7 , and 5.2 × 10 −6 m s −1 , respectively [57].…”
Section: Resultsmentioning
confidence: 64%
“…1B. Formation of liposomes from a film of ultra-low melting agarose hence led to giant liposomes with comparable, low-permeability-characteristics than liposomes prepared by other methods [55,58]. …”
Section: Resultsmentioning
confidence: 99%
“…These have found wider application in drug delivery as they can resist GIT peristalsis movements due to stronger covalent binding of thiol groups of polymers with cysteine-rich components of mucus [89]. Thiomers also possess the capability to bind to the transmembrane domain of P-gp and thus enabling higher delivery of P-gp substrate drugs [90]. In vitro studies revealed that thiomer (cysteine) conjugation onto the surface of docetaxel-loaded NLCs using postinsertion technique led to higher mucoadhesion (81.6%) with mucin in comparison to unconjugated NLCs (51.9%) [76].…”
Section: Engineered Nlcsmentioning
confidence: 99%
“…20 Secondly, thiomers produced increased permeation, which can improve drug transport across the intestinal epithelial cells. 21 Thirdly, they can inhibit the P-gp activity in the intestinal epithelium, due to the interaction of the thiol groups with the transmembrane domain of the efflux pump, 22,23 which is very important for the influx of the majority of anticancer drugs into intestinal epithelium cells.…”
Section: Introductionmentioning
confidence: 99%